(3MGTjI GdESbGWj Ydi TQM edGeScjf Ydi GdcfRs - (3CHhGdYHGS CMeO Hf YeQ GdESbGWjs; (3YHO Gddg Hf CMeO Hf eMehO GdfSaj, CHh GdHQcGJ, MGaX GdOjf,J (B710 (3g` s
(3ChdgG (B:s
(3ebGHdI JLejY GdYWGI GdJj JhLO aj GdfcGM s
(3BNQgG (B:s
(3hgj Mb GdYHO NGdUkG hGddg JYGdi CYde Gdehab ddUhGH Je GdLRA GdChd HMeO Gddg hYhfg hMSf Jhajbg hUi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg hSde JSdjekG cKjQkG s
(3dg HbjI ef Chdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B32s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1515s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3Gdabg GdMfajs